(untitled) (Ágora de Heterodoxias, 2023)
This article explains in general lines the main contributions made by different authors on the management of service quality models to supermarkets, starting from the approach of each author, examining the main problems in the evaluation of service quality. Also identifies the main dimensions and/or attributes necessary for measurement, as well as the techniques and instruments used, in addition to the type of research carried out. As a result of the analysis carried out, a set of determining and relevant aspects emerge for proposing new alternative models for verifying service ownership in supermarkets, as well as the identification of eight key quality attributes that correspond to different facets of the customer service process and that should be taken into account for future research in the area.